2018
DOI: 10.1111/ped.13709
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and epidemiology of pediatric ventriculoperitoneal shunt infection

Abstract: Background The aim of this study was to identify independent risk factors for cerebrospinal fluid shunt infection. Methods The medical records of all patients aged 0–18 years who underwent shunt‐related surgery for the treatment of hydrocephalus at the present institution between January 1996 and December 2015 were reviewed. For each case, two randomly selected controls with no shunt infection, matched for year of surgery, were chosen. Demographic clinical and microbiological data were abstracted. Results A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
43
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 22 publications
4
43
1
1
Order By: Relevance
“…Regression analysis did not reveal that factors such as age, gender or aetiology to be independent risk factors for the occurrence of revision surgery due to infection, unlike other previous studies [ 17 ]. Other reports have also indicated that subsequent shunt revisions increase the risk of further shunt infections in paediatric patients [ 3 ]. Proximal failure and misplacement (either proximally or distally) came close as the second most common cause for primary revision.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis did not reveal that factors such as age, gender or aetiology to be independent risk factors for the occurrence of revision surgery due to infection, unlike other previous studies [ 17 ]. Other reports have also indicated that subsequent shunt revisions increase the risk of further shunt infections in paediatric patients [ 3 ]. Proximal failure and misplacement (either proximally or distally) came close as the second most common cause for primary revision.…”
Section: Discussionmentioning
confidence: 99%
“…V entriculoperitoneal )VP( shunt insertion is one of the most common procedures in pediatric neurosurgery for treating hydrocephalus. 1 Among pediatric age group hydrocephalus is considered a common, surgically correctable condition in which there is an increase in the volume cerebrospinal fluid )CSF(, leading to cerebral ventricles dilatation, thinning of the cerebral mantle, and elevation of intracranial pressure. 2 Patients with VP shunts represent more than 30,000 hospital admissions per year.…”
mentioning
confidence: 99%
“…2 Although VP shunting has decreased the morbidity and mortality of hydrocephalus, it is still associated with multiple complications, many of which require surgical revision. [1][2][3][4] Recent studies have reported the rate of complications following VP shunting to be between 30% and 50%. [3][4][5][6] Shunt malfunctions causes can be categorized into infectious, mechanical, or functional.…”
mentioning
confidence: 99%
See 2 more Smart Citations